SYSTEMIC FUNCTIONAL TRANSLATION STUDIES (SFTS): THE THEORY TRAVELLING IN BRAZILIAN ENVIRONMENTS - Vasconcellos, Maria Lúcia (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
This paper presents a mapping of the Systemic Functional Translation Studies (SFTS) tradition in the Brazilian environment, from its genesis up to developments in the 2000’s. While studies during the earlier period are informed by the concept of “translation as (re)textualization”, more recent SFTS research can be charted along the ‘cline of instantiation’, translations being investigated as “instantiations-incontexts”, cross-lingual functional varieties of language, or still as sources of SFL-based language description of Brazilian Portuguese. From late 90’s on, computerized corpora and corpus-based methodologies have been integrated into Brazilian SFTS, for which annotation methods for the tagging of SFL categories have been developed. The paper ends with a consideration of Brazilian SFTS against the background of international SFTS as disseminated in the 2nd HCLS.